Health Systems in Australia and Four Other Countries: choices and challenges - Jo M Martins (ACHSM, 2016)
The purpose of health systems is the pursuit of healthy lives. The performance of the Australian health system over the last decade is compared with the United Kingdom and its three other offshoots: the United States, Canada and New Zealand. In the first instance, system performance is assessed in terms of threats to healthy lives from risk factors and changes that have taken place during the decade. In view of the emphasis of the five systems on the return to health after trauma and illness, and the human-resource intensity of health services, an appraisal is made of changes in the number of the major health professionals in relation to the growing populations. Then related changes in hospital, medical practitioner and dentist services are assessed. Changes in pharmaceutical drug prescriptions in Australian are also examined. The levels of national expenditures arising from the provision health services are then considered in the context of the costs of administration of the varied organisational modes, use of expensive medical technologies, pharmaceutical drug consumption and remuneration of health professionals. Finally, health outcomes in Australia and the other four countries are assessed in accordance with their human development level, life expectancy, potential years of life lost from different causes, as well as healthy life expectancies. Further, gaps in health and life expectancy of Indigenous people in the United States, Canada, New Zealand and Australia are reviewed, as well as health and survival inequalities among people in different social strata in each country. Abbreviations: GDP - Gross Domestic Product; HDI - Human Development Index.